O fim do paraíso fiscal Sul-Americano: o processo decisório uruguaio - Barbosa, Márcio Roberto da Costa (2014)
Uruguay, previously known as the “South American Switzerland”, adopted the tax haven model. Nevertheless, with the Tax Reform (Law No. 18.083) passed in 2007, the country abandoned this model. The question that this paper aims to answer is the reason for the political decision taken by the country to stop being a tax haven. The hypothesis raised for this investigation was subdivided in two planes. Externally, the scenario was one of version to tax havens and the pressure exerted over them. Internally, the motive would be the difficulty of establishing compatibility between a leftist government and a tax haven model. It was exactly when a political party with this ideology came into power that the reform was accomplished. This case study used documents as supporting data. The theory that erved as basis for this analysis is found on the work An Economic Theory of Democracy, by Anthony Downs and such theory was in part confirmed empirically. Regarding the ypothesis, and taking into consideration the international standpoint, an adverse nternational scenario served as confirmation of the country‟s decision. The same cannot be said about the internal scenario, in which the issue of ideology was not shown to be a determining factor for the decision which is the object of this study.